A tale of Sustainability and Equity: defining a safe operating space for households’ energy vulnerability. - Martellozzo, Federico (European Journal of Sustainable Development, 2017)
The demand for natural resources to sustain human activities has dramatically increased in recent decades; as a consequence, we have potentially reached peak oil, poisoned much of the remaining natural ecosystem, and irreversibly compromised the atmosphere. The consequences of the increased anthropogenic pressure on the natural environment have forced us to confront the paradoxical coexistence of two factors required to sustain the development of a growing population: the need to access a larger natural resource base and the need to increase resilience by alleviating human pressure on the natural environment. Thus, limiting energy consumption, or increasing consumption efficiency, is a matter of urgent concern in decelerating the anthropogenic depauperation of the natural environment. Policy making has often interpreted this problem within a technical-reductionist framework. This mainstream perspective has led to neglect issues pertaining resilience and justice thus creating a fertile ground for the appearance of new forms of poverty, which affect not solely developing countries but also the western world. This study focuses in particular on fuel poverty, and its aims are threefold: revitalize the critics to the implicit unsustainable and inequitable principles conveyed through the technical-reductionist approach; elaborate an alternative methodological framework based on equitable and sustainable paradigms; discuss how this can support policy makers in identifying relevant areas for public intervention. Keywords: energy vulnerability; Ile-de-France, sustainability, equitable development, spatial justice, energy needs.